2009
DOI: 10.1017/s0266462309990365
|View full text |Cite
|
Sign up to set email alerts
|

Quality of trials reported as conference abstracts in China: How well are they reported?

Abstract: The information given for trials in conference proceedings in China is very poor, especially in some aspects of methodological quality, trial registration, and funding source. The quality of conference abstracts for trials should be improved to further facilitate understanding of their conduct and validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In several studies, it was reported that the information given for trials in conference proceedings is far from being optimal [18,19]. Clear, transparent and accurate reporting or research is important because it enables readers to understand what was done and to acess the applicability and relevance of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, it was reported that the information given for trials in conference proceedings is far from being optimal [18,19]. Clear, transparent and accurate reporting or research is important because it enables readers to understand what was done and to acess the applicability and relevance of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Because of our search strategy, we recovered a number of Chinese language studies, most of which were found through extensive searching in Google and Google Scholar. Some studies have noted the poor quality of reporting of randomised controlled trials in leading medical journals and conference proceedings in China (Xu 2008;Duan 2009;). One study found that only 6.8% of apparent randomised controlled trials in China were authentic randomised controlled trials (Wu 2009).…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…The reporting quality of these abstracts is important because systematic reviewers will in some situations decide to include a study (or not) based on the conference abstract because the full article is not available. The reporting quality of conference abstracts was assessed in different topics in health, including sports injury prevention, oncology, urology, psychiatry, surgery, and oral health [6][7][8][9][10][11][12][13] . However, there are no studies assessing abstracts of systematic reviews in dentistry published in the proceedings of conferences.…”
Section: Introductionmentioning
confidence: 99%